Parental warmth, rejection, and creativity: The mediating roles of openness and dark personality traits. (1st January 2021) - Guo, Jiajun; Zhang, Jing; Pang, Weiguo
Abstract: Family plays an important role in shaping one's creativity. In the current study, 559 college students, ranging from 18 to 30 years of age, were recruited to complete a survey measuring perceptions of their parents' rearing styles (warmth & rejection), personality traits (openness & the dark triad, including narcissism, Machiavellianism, & psychopathy), and creativity (originality, creative activities, & creative achievements). Using structural equation modeling, we found that both parental warmth and parental rejection were positively associated with creativity. More importantly, openness fully mediated the influence of warmth on all the indices of creativity. However, only Machiavellianism, of the three dark traits, served as a partial mediator between the effects of parental rejection on creative activities. Results are further discussed from the perspective of eastern-western cultural differences.